Development of High-performance Proton Transfer Reaction Time-of-Flight Mass Spectrometer - Chun-guang XIE; Ji-yang ZHANG; Tong YANG; Yu-liang HUANG; Shu-guang XIE; Hui ZHU; Jing-xuan SUN; Ping CHENG (Zhipu Xuebao)
This paper introduced a homemade high-performance proton transfer reaction time-of-fight mass spectrometer (PTR-TOF MS), which can be used for real-time online analysis and monitoring of complex organic gas mixtures. Proton transfer reaction ionization is one of the typical methods of “soft” ionization techniques, which generally takes water and hydronium ions as parent ions, and the objects which have higher proton affinity than water can be ionized. By integrating an orthogonal-injection reflectron time-of-flight mass analyzer and a micro-channel plate detector, the instrument’s resolution and sensitivity are significantly enhanced，with the characteristics of high sensitivity, a wide mass detection range, a low detection limit, a wide linear range and little sample pretreatment. The system is mainly composed of hollow cathode discharge ion source, proton transfer reaction tube, high efficiency ion transport region and high-performance time-of-flight mass analyzer. To reduce ion loss during transmission, improve system performance and ensure the stability of vacuum at all levels, the system adopts a four-stages of differential vacuum design, with the first stage being the proton transfer reaction tube, the second stage being the radio frequency quadrupole ion transport region, the third stage being the direct current quadrupole ion transport region, and the fourth stage being the time-of-flight mass analyzer. Based on the proton affinity of the reaction reagent ions, the system can analyze the majority of VOCs while excluding interference from air components. Experimental tests showed that the system’s resolution (full width half maximum, FWHM) is better than 2 069 (for toluene), with the detection limit of 0.36 μg/m3, a linear range of 4 orders of magnitude, and a linear correlation coefficient (R2) of 0.991. The development of this system provides a new method for online rapid analysis of VOCs in environmental monitoring, industrial processes, and biomedicine, accelerating the technical development of PTR-TOFMS domestically and narrowing the gap with the international advanced level.